Enhancing arbuscular mycorrhiza symbiosis effectiveness through the involvement of the tomato GRAS transcription factor SCL3/SlGRAS18 - Avilés-Cárdenas, Jonathan; Molinero-Rosales, Nuria; Pérez-Tienda, Jacob; Rosas-Díaz, Tábata Victoria; Castillo-Garriga, Araceli; García-Garrido, José M. (Elsevier, 2024)
Arbuscular mycorrhizal (AM) fungi improve plant growth, nutrition, fitness and stress tolerance while AM fungi obtain carbohydrates and lipids from the host. This whole process of mutual benefit requires substantial alterations in the structural and functional aspects of the host root cells. These modifications ultimately culminate in the formation of arbuscules, which are specialized intraradical and highly branched fungal structures. Arbuscule-containing cells undergo massive reprogramming to hosting arbuscule and members of the GRAS transcription factor family have been characterized as AM inducible genes which play a pivotal role in these process. Here, we show a functional analysis for the GRAS transcription factor SCL3/SlGRAS18 in tomato. SlGRAS18 interacts with SlDELLA, a central regulator of AM formation. Silencing of SlGRAS18 positively impacts arbuscule development and the improvement in symbiotic status, favouring flowering and therefore progress in the formation and development of fruits in SlGRAS18 silenced plants which parallel to a discernible pattern of mineral nutrient redistribution in leaves. Our results advance the knowledge of GRAS transcription factors involved in the formation and establishment of AM symbiosis and provide experimental evidence for how specific genetic alterations can lead to more effective AM symbiosis
Keywords: Virus fitopatógenos; Arbuscular mycorrhiza; GRAS transcription factor; Symbiosis effectiveness; Arbuscule